Interfacial electronic regulation of zeolite sites via heterojunction toward efficient electrocatalysis in lithium-sulfur batteries - Hao Meng; Xi Liu; Chengjiao Zhao; Xin Yang; Yihang Nie; Zhen Chen; Lin Yang; Jiayi Wang; Xin Wang; Mingliang Jin; Zhongwei Chen (Chemical Engineering Journal, 2026)

Efficient phosphate removal and flocculation of Microcystis aeruginosa via a flower-like spherical Metal-Organic Framework La-BDC-NH2: Investigation of performance and mechanism - Jinyun Guan; Dandan Wang; Xiaozheng Ma; Ruoxin Wang; Lin Dang; Yihang Sun; Yichenyang Li; Jifeng Guo (Chemical Engineering Journal, 2026)

Rooftop wind field reconstruction using sparse sensors: From deterministic to generative learning methods - Yihang Zhou; Chao Lin; Hideki Kikumoto; Ryozo Ooka; Sibo Cheng (Building and Environment, 2026)

Evaluating the role of onboard carbon capture and storage system in remedial unit balancing under the IMO net-zero framework: Insights from GFI and 4E analysis - Yihang Zhou; Shuai Deng; Zhen Tian; Ke Li; Meng Lin; Li Zhao; Chunfeng Li; Xiaohan Zhao; Yijiang Tian; Wenjing Zhang; Min Shi (Journal of Cleaner Production, 2026)

A “three birds with one stone” strategy: Light-switchable chitosan film via natural supramolecular co-assembly for enhanced fruit preservation - Zhiwei Wang; Jihui Lu; Jichang Wei; Yihang Zhao; Yiqing Huang; Shuchang Yao; Xinru Tan; Xiaoyu Lin; Xuemei Huang; Penglong Wang (Chemical Engineering Journal, 2026)

Performance of PEI-modified fumed silica monoliths with honeycomb structure for direct air capture of CO2 - Chenyang Lin; Yijun Wang; Yihang Liu; Takeshi Hagio; Baowen Zhou; Xinling Li; Zhen Huang (Gas Science and Engineering, 2026)

Graphene-enhanced perfluorosilane coating with an ultralow sliding angle prevents lunar dust adhesion - Xin Wang; Zekai Huang; Sheng Chen; Yue Ouyang; Shengyu Wu; Lingjun Wu; Jinwei Zhao; Yihang Wang; Shengyuan Dai; Yani Lin; Yi Wang; Zhigui Liu; et al. (Chemical Engineering Journal, 2026)

Soil calcium ion enrichment associated with altered microbial functional gene networks in bamboo forest expansion - Yaoxing Wu; Huimin Tian; Jiahuan Guo; Yawen Shen; Qingqing Liu; Lin Yu; Zhiyin Tang; Yihang Jia; Gong Zhang; Jun Deng; Lianghua Qi (Applied Soil Ecology, 2026)

PIV study of turbulence characteristics in resonant sloshing within a rectangular tank with a vertical perforated baffle - Yihang He; Lian Tang; Pengzhi Lin (Ocean Engineering, 2026)

A machine learning and box modeling approach to comparing the atmospheric chemistry of high- and low-ozone and PM₂.₅ episodes - Ahsan Mozaffar; Yan-Lin Zhang; Yihang Hong; Mei-Yi Fan; Yu-Chi Lin (Atmospheric Research, 2026)

Advancing Non‐Contact Fish Phenotyping via Optical Sensing: Toward Precision Aquaculture - Kai Lin; Shiyu Zhang; Wei Wang; Tian Dong; Wen Ding; Chenfan Geng; Yihang Lu; Hongxia Hu (Reviews in Aquaculture, 2026)
Non‐contact fish phenotyping has become an essential strategy for precision aquaculture, enabling accurate, high‐throughput, and non‐invasive trait measurement. In this review, a digital phenotyping framework is summarized, including application‐driven trait definition, multimodal data acquisition (2D, 2.5D, and 3D imaging), and automated phenotypic analysis based on computer vision and deep learning. According to current research paradigms, optical phenotyping applications are systematically categorized into three major domains: morphological, behavioral, and appearance‐based phenotyping. Multimodal optical sensing systems now support high‐throughput morphological, behavioral, and appearance‐based phenotyping, enabling applications ranging from biomass estimation and intelligent feeding control to selective breeding, product quality evaluation, species identification, and disease diagnosis. Despite rapid methodological progress, most existing studies remain confined to laboratory or semi‐controlled environments, and large‐scale implementation in commercial production systems is still limited. Key challenges persist in underwater image degradation, posture‐induced measurement uncertainty, data heterogeneity, model generalizability, computational constraints, and the integration of phenotypic and genomic data for precision breeding. Finally, future development pathways are discussed, including efficient and flexible data acquisition platforms, lightweight and real‐time processing, transfer and few‐shot learning, multimodal data fusion, novel phenotype quantification, and standardized open datasets. Based on a comprehensive analysis of over 100 studies, this review maps the current technological landscape and proposes pathways toward scalable, intelligent phenotyping systems that can improve fish welfare, enhance breeding efficiency, and promote sustainable aquaculture management.

Dynamic snake vision mask r-cnn: a method for microfracture detection in electrical logging imaging - Yihang Lu; Sinan Fang; Yi Yu; Huimin Wu; Guilan Lin; Guohao Ma; Zehan Wang (Earth Science Informatics, 2025)

Smartphone-assisted Ce-POM/CuBTC peroxidase-like colorimetric detection of H2O2 and ascorbic acid in food samples - Yiyi Zhang; Haibo Zhang; Chengyuan Ma; Yihang Yang; Xuan Mo; Yuan Shi; Zhijia Yin; Hong Li; Lin Sun (Food Chemistry, 2025)

A GTPase activating protein Polrg1 regulates the development and cellulase expression of Penicillium oxalicum - Shuai Li; Wenchao Chen; Zhimin Shi; Lin Xu; Ziyin Xu; Yihang Qu; Yu Wang; Chunna Sun; Mei Chen; Zhonghai Li (World Journal of Microbiology and Biotechnology, 2025)

A Rho-Type GTPase Protein Pocdc42 Regulates the Development and Cellulase Expression of Penicillium oxalicum - Shuai Li; Wenchao Chen; Zhimin Shi; Ziyin Xu; Lin Xu; Yu Wang; Yihang Qu; Chunna Sun; Mei Chen; Zhonghai Li (Current Microbiology, 2025)

The 14–3–3 gene AaGRF1 positively regulates cold tolerance in kiwifruit - Zhang Zhenzhen; Li Sumei; Sun Shihang; Li Hongli; Zhang Qina; Li Yihang; Li Yukuo; Liu Mingyu; Li Congcong; Sun Leiming; Lin Miaomiao; Qi Xiujuan (Plant Science, 2025)

GRACE/ML-based analysis of the spatiotemporal variations of groundwater storage in Africa - Kuiyuan Ding; Xiaowei Zhao; Jianmei Cheng; Ying Yu; Yiming Luo; Joaquin Couchot; Kun Zheng; Yihang Lin; Yanxin Wang (Journal of Hydrology, 2025)

Experimental investigation of slamming pressure on 3D bow flare - Yihang Shan; Hui Li; Bingbing Han; Zhiyong Sun; Lin Lu; Ruixiang Liu; Yi Liu; Hao Guo (Ocean Engineering, 2024)

Important contributions of natural gas combustion to atmospheric nitrate aerosols in China: Insights from stable nitrogen isotopes - Yu-Chi Lin; Mei-Yi Fan; Yihang Hong; Mingyuan Yu; Fang Cao; Yan-Lin Zhang (Science Bulletin, 2024)

Optimization framework for daylight and thermal environment of retractable roof natatoriums based on generative adversarial network and genetic algorithm - Zhongqi Yu; Xinyi Ge; Zhaoxiang Fan; Yihang Zhou; Dawei Lin (Energy and Buildings, 2024)

Experimental study on improving effect of cooling garment on thermal comfort and EEGs - Huxiang Lin; Haiying Wang; Renjie Yan; Junli Sun; Hang Meng; Songtao Hu; Yihang Ji (Building and Environment, 2024)

Development of antioxidant sodium alginate gel beads encapsulating curcumin/gum Arabic/gelatin microcapsules - Yihang Lin; Jiachao Xu; Xin Gao (Food Hydrocolloids, 2024)

Sulfur bacteria-reinforced microbial electrochemical denitrification - Sen Lin; Wentao Tang; Yihang Xiao; Feixiang Zan; Xiaoming Liu; Guanghao Chen; Tianwei Hao (Bioresource Technology, 2024)

Preparation of site-specific Z-scheme g-C3N4/PAN/PANI@LaFeO3 cable nanofiber membranes by coaxial electrospinning: Enhancing filtration and photocatalysis performance - Yihang Mao; Li Lin; Yuexing Chen; Mingrui Yang; Li Zhang; Xianxiang Dai; Qing He; Yuanyuan Jiang; Hui Chen; Jinqiu Liao; Yunsong Zhang; Ying Wang (Chemosphere, 2023)

Is hand-to-mouth contact the main pathway of children’s soil and dust intake? - Yiwei Gong; Yihang Wu; Chunye Lin; Dongqun Xu; Xiaoli Duan; Beibei Wang; Xitao Liu; Hongguang Cheng; Qin Wang; Jin Ma (Environmental Geochemistry and Health, 2022)

Research on cropping intensity mapping of the Huai River Basin (China) based on multi-source remote sensing data fusion - Yihang Wang; Lin Fan; Ranting Tao; Letao Zhang; Wei Zhao (Environmental Science and Pollution Research, 2022)

Theoretical evaluation of group delay on pseudorange bias - Yuqi Liu; Lin Chen; Yi Yang; Hongchen Pan; Yihang Ran (GPS Solutions, 2019)